New prophylaxis regimen for SARS-CoV-2 infection in health professionals with low doses of hydroxychloroquine and bromhexine: a randomised, double-blind placebo clinical trial (ELEVATE Trial) - Julio Granados-Montiel; Eric Hazan-Lasri; Rafael Franco-Cendejas; Tatiana Chávez-Heres; Phaedra Silva-Bermudez; Rocio Aguilar-Gaytán; Natalia Manzano-León; Karla Méndez-Maldonado; Alejandro Alvarez-Arce; Raigam Jafet Martínez-Portilla (BMJ Open)
Introduction SARS-CoV-2 infection in Mexico has caused ~2.7 million confirmed cases; around 20%–25% of health workers will be infected by the virus at their workplace, with approximately 4.4% of mortality. High infectivity of SARS-CoV-2 is related with cell entry mechanism, through the ACE receptor. SARS-CoV-2 requires transmembrane protease serine 2 to cleave its spike glycoprotein and ensure fusion of host cell and virus membrane. We propose studying prophylactic treatment with hydroxychloroquine (HCQ) and bromhexine (BHH), which have been shown to be effective in preventing SARS-CoV-2 infection progression when administered in early stages. The aim of this study is to assess the efficacy of HCQ and BHH as prophylactic treatments for SARS-CoV-2 infection in healthy health workers exposed to the virus.Methods and analysis Double-blind randomised clinical trial, with parallel allocation at a 1:1 ratio with placebo, of low doses of HCQ plus BHH, for 60 days. Study groups will be defined as follows: (1) HCQ 200 mg/day+BHH 8 mg/8 hours versus (2) HCQ placebo plus BHH placebo. Primary endpoint will be efficacy of both interventions for the prevention of SARS-CoV-2 infection, determined by the risk ratio of infected personnel and the absolute risk. At least a 16% reduction in absolute risk is expected between the intervention and placebo groups; a minimum of 20% infection is expected in the placebo group. The sample size calculation estimated a total of 214 patients assigned: two groups of 107 participants each.Ethics and dissemination This protocol has been approved by the local Medical Ethics Committee (National Institute of Rehabilitation ‘Luis Guillermo Ibarra Ibarra’, approval number INRLGII/25/20) and by the Federal Commission for Protection against Sanitary Risks (COFEPRIS, approval number 203 300 410A0058/2020). The results of the study will be submitted for publication in peer-reviewed journals and disseminated through conferences.Trial registration number NCT04340349.